Genetic typing of bovine viral diarrhea virus isolates from Costa Rica - Chaves, A. (2012)
Sixteen bovine viral diarrhea virus (BVDV) isolates collected in Costa Rica between 1987 and 2006 from dairy cattle were analyzed by RT-PCR and determined to belong to BVDV species 1. Furthermore, eleven of these isolates were genotyped using the nucleotide sequences of the Npro region of the viral genome. Phylogenetic analysis indicated that all samples examined clustered within the BVDV-1b subtype.